A generic framework for real-time multi-channel neuronal signal analysis, telemetry control and sub-millisecond latency feedback generation - Zrenner, Christoph; Eytan, Danny; Wallach, Avner; Thier, Peter; Marom, Shimon (Frontiers in Neuroscience, 2010)
Distinct modules of the neural circuitry interact with each other and (through the motor-sensory loop) with the environment, forming a complex dynamic system. Neuro-prosthetic devices seeking to modulate or restore CNS function need to interact with the information flow at the level of neural modules electrically, bi-directionally and in real-time. A set of freely available generic tools is presented that allow computationally demanding multi-channel short-latency bi-directional interactions to be realized in in-vivo and in-vitro preparations using standard PC data acquisition and processing hardware and software (Mathworks Matlab and Simulink). A commercially available 60-channel extracellular multi-electrode recording and stimulation set-up connected to an ex-vivo developing cortical neuronal culture is used as a model system to validate the method. We demonstrate how complex high-bandwidth (> 10 megabit per second) neural recording data can be analyzed in real-time while simultaneously generating specific complex electrical stimulation feedback with deterministically timed responses at sub-millisecond resolution.